Pengembangan Asesmen Pengetahuan Pendidikan Agama Islam Berbasis HOTS (Higher Order Thinking Skills): Dari Hafalan Menuju Pemahaman Mendalam - Nurul Maidah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The transformation of 21st-century education demands a shift in assessment paradigms—from merely measuring memorization to evaluating higher-order thinking skills. In the context of Islamic Religious Education (PAI), assessments that focus solely on memorizing texts and religious references are no longer sufficient to address contemporary challenges. This study aims to explore strategies for developing knowledge assessment instruments in PAI based on Higher Order Thinking Skills (HOTS). Using a qualitative approach through library research, the author examines various theoretical sources and educational policies. The findings indicate that the application of the revised Bloom’s Taxonomy serves as a primary foundation in developing HOTS-based questions. Ideally, HOTS assessments in PAI should include indicators of analysis, evaluation, and creation, connected to real-life situations and spiritual values. This study recommends that PAI teachers design assessments that encourage students to think reflectively, contextually, and critically about Islamic teachings.